Մեղքի և ապաշխարանքի գրոտեսկային ենթատեքստը Գ.Գրասի «Թիթեղյա թմբուկը» վեպում - Սյուզաննա Նավասարդյան (ՀՀ ԳԱԱ հրատ.)
The article deals with the analysis of grotesque implication of guilt and repentance in the G.Grass՛ novel "The Tin Drum". It is the best prose work of the greatest modem German writer, for what he got a Nobel prize. The idea of guilt, connected with the historical past, is veiled here - in grotesque characters and scenes - in the deeper layers and in the implication of the novel. This article is an attempt to bring to light that implication and to show up the main aim of G.Grass, that is to deride and tocriticize nationalism and the idea of war in general.
Keywords: Language and Literature